Augmented Reality-Enabled WebGIS for Navigation and Decision Support of Potential Kawakawa (Euthynnus affinis) Fishing Zones - Ayang Armelita Rosalia; Luthfi Anzani; Denta Tirtana; Bagus Firmansyah; Harini Najla Azizah; Najwa Nur Hafazah; Rachel Palupi (International Journal of Marine Engineering Innovation and Research, 2026)
Efficient identification of potential fishing zones is crucial for sustainable coastal fisheries. This study presents the integration of oceanographic data analysis, spatial modeling, and Augmented Reality (AR) technology to predict and visualize suitable fishing locations for Euthynnus affinis in the waters of Panjang Island, Banten, Indonesia. Sea surface temperature (SST) and chlorophyll-a concentrations were derived from MODIS satellite imagery and processed using Google Colaboratory to generate spatial distribution maps of key environmental parameters. These maps formed the basis for predicting potential fishing zones, which were implemented in NaviAR, a WebGIS-based platform with AR features that provides interactive visualization, real-time coordinates, distance measurements, and directional markers toward predicted fishing locations. The system’s main features, including the Home page, AR Camera, and WebGIS modules, were tested using black-box testing, achieving a 100% functional success rate. These results indicate that NaviAR effectively supports decision-making for fishermen by providing spatially explicit and actionable information on potential fishing zones